Restrição alimentar em cordeiros terminados em confinamento - Cavilhão, Cristiani (2013)
It was aimed with this study to evaluate the different levels effect of feed restriction on performance, intake, digestibility and feeding behavior of feedlot finished lambs, besides the economic viability of this feed management type . For this, 24 Santa Inês male lambs were used, to 20.00 ± 0.32 kg body weight distributed in an entirely randomized design in four different treatments. The experiment was divided into periods of 64 days each, in the first called restriction, the animals were assigned to treatments: no restriction (ad libtum intake with 10% leftovers), restriction of 20, 40 and 60 % in relation to intake of the control treatment. In the second period, called refeeding period, the diet was offered ad libitum to all animals in the experiment. Data were subjected to the variance analysis F test and when significant differences were detected, the regression analysis was used to study the food restriction levels. All statistical procedures were evaluated at 5 % probability. Feed restriction affected negatively the animals performance in all periods . There was a linear decrease in the intake of dry matter and nutrients throughout the experiment . No effects of dietary restriction on eating behavior were identified, except for time spent with feeding that was significantly reduced . The apparent digestibility of dry matter and nutrients did not differ statistically , except in the fiber digestibility in neutral detergent that linearly increased in the restrictive period with the imposed restriction levels . The food restriction management is economically viable in feedlot lambs production for 128 days